2015
DOI: 10.1007/s11669-015-0377-3
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of Mobilities and Diffusion in Ti-Sn Alloy

Abstract: Based on the thermodynamic parameters and experimental diffusion data in the literature, the atomic mobilities of bcc Ti-Sn alloys are assessed by the CALPHAD method using DICTRA software package, and boundary mobility parameters of hcp Ti-Sn alloys were also given in the work. Compared with the calculated and measured diffusion coefficients of bcc Ti-Sn, most of the experimental data are reproduced well. The composition-distance profiles of Ti/Ti-4.9 at.% Sn diffusion couple at 1223 K for 14.4 ks were also pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Therefore, Ti alloys are modified to have improved mechanical properties by adding different stabilizers such as neutral (Tin and Zirconium) stabilizers, alpha (Aluminum, Oxygen, Nitrogen, and Carbon) stabilizers, beta isomorphous (Molybdenum, Vanadium, Tantalum, Niobium) stabilizers, and beta eutectoid (Iron, Manganese, Chromium, Cobalt, Nickel, Copper, Silicon, and Hydrogen) stabilizers [16][17][18]. The alpha stabilizers exhibit good corrosion resistance; beta isomorphous elements exhibit complete solubility with the Ti and form an intergranular beta phase that limits the ductility; beta eutectoid elements exhibit incomplete solubility with Ti Molecules 2021, 26, 2894 2 of 13 and make it brittle [19][20][21]. According to the hardening effects of the isomorphous beta stabilizers (Mo, V, Ta, Nb), Mo has been proved to be more effective in strengthening Ti alloys than V, Ta, and Nb addition [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Ti alloys are modified to have improved mechanical properties by adding different stabilizers such as neutral (Tin and Zirconium) stabilizers, alpha (Aluminum, Oxygen, Nitrogen, and Carbon) stabilizers, beta isomorphous (Molybdenum, Vanadium, Tantalum, Niobium) stabilizers, and beta eutectoid (Iron, Manganese, Chromium, Cobalt, Nickel, Copper, Silicon, and Hydrogen) stabilizers [16][17][18]. The alpha stabilizers exhibit good corrosion resistance; beta isomorphous elements exhibit complete solubility with the Ti and form an intergranular beta phase that limits the ductility; beta eutectoid elements exhibit incomplete solubility with Ti Molecules 2021, 26, 2894 2 of 13 and make it brittle [19][20][21]. According to the hardening effects of the isomorphous beta stabilizers (Mo, V, Ta, Nb), Mo has been proved to be more effective in strengthening Ti alloys than V, Ta, and Nb addition [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that the Sn-Ti alloy with a Ti content of less than 6% can react with quartz glass at welding temperature to form a compact interfacial layer [9]. Studies on Sn-Ti alloy have been widely reported [10][11][12][13][14][15][16][17][18][19][20][21][22], and Sn-Ti alloy has been used to weld sapphire, diamond grits, zirconia or Poly-Crystalline CVD Diamond Plates in recent years [18][19][20][21][22]. However, almost no reports have focused on Sn-Ti alloy for quartz glass-metal welding except for our previous work [9].…”
Section: Introductionmentioning
confidence: 99%
“…Even though, by the addition of α stabilizer elements only concentrating on corrosion resistance, β eutectoid elements can bring the brittle compound phase, and the β isomorphous elements form the intergranular β phase that limits the ductility, strengthening effect, and the high-temperature performance. Limited strengthening effects and high cost restricted the large-scale production in the field of applications [24][25][26]. The previous researchers demonstrated that a neutral alloying element like Sn has a large solubility so that the mechanical properties are greatly improved [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Limited strengthening effects and high cost restricted the large-scale production in the field of applications [24][25][26]. The previous researchers demonstrated that a neutral alloying element like Sn has a large solubility so that the mechanical properties are greatly improved [24][25][26]. Hsu et al [24] investigated that elasticity, bending modulus, and bending strength of the casting (Ti-Sn alloy) were higher than for commercial pure titanium alloy.…”
Section: Introductionmentioning
confidence: 99%